(untitled) (Albayan Scientific Journal, 2023)
The study was conducted on three pregnant camel (6-8 years of age) selected by birth, who were present in the natural pastures of the Heisha project for one year from the moment of parturation. The aim of the study is to determine the effect of the seasons and months on white blood cells and their differential count. The results in this study were no moral differences (p < 0.05) for the total number of white blood cells (WBC) during the seasons. Neutrophil was morally high (p < 0.05), during the summer and autumn of winter and spring. Lymphocyte was morally elevated (p < 0.05) in the spring from other seasons. Monocyte and Basophil in autumn were morally high (p < 0.05) for spring and summer. There are no differences in eosinophil during the seasons. The effect of the months was as follows: the total number of white blood cells (WBC) is morally high (p < 0.05) at birth (January) and in both the first and fourth months compared to the other months and stability from the eighth month to the end of the trial. Neutrophil at birth and from the fifth to eighth months were morally high significant (p < 0.05) than the rest of the months. Lymphocyte was low significant at birth (p < 0.05), the highest value in the trial, at the third month, and then from the fifth month to the end of the study, no significant differences between them but were low significant (p < 0.05) from the months before. Monocyte is low significant (p < 0.05) at birth and then began to rise during the first month and then the ratio of monocyte decreased significantly (p < 0.05) to the ninth month, after which in the tenth month the ratio increased significantly (p < 0.05) for all months of study. The ratio of Eosinophil is low significantly (p < 0.05) in both the birth and the first month, which increases gradually from the second month to reach the highest moral high (p < 0.05) in this trial at the fifth month. The ratio of basophil cells is morally low (p < 0.05) from birth to the fourth month and from the tenth month to the end of the study is morally high (p < 0.05) from the rest of the trial months.